1992
DOI: 10.1128/aem.58.9.2866-2873.1992
|View full text |Cite
|
Sign up to set email alerts
|

Formation of poly(hydroxybutyrate-co-hydroxyvalerate) by Azotobacter vinelandii UWD

Abstract: Azotobacter vinelandii UWD formed polyhydroxyalkanoate (PHA) copolymers containing 13-hydroxybutyrate and 13-hydroxyvalerate (HV) when grown in a medium containing glucose as the primary C source and valerate (pentanoate) as a precursor. Copolymer was not formed when propionate was added to the glucose medium but was formed when heptanoate, nonanoate, or trans-2-pentenoate was present. Optimal levels of HV were formed when valerate was added at the time of maximum PHA synthesis, although HV incorporation was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 34 publications
6
52
1
Order By: Relevance
“…1 g 1-~ hthe rate of HV synthesis was constant (approx. 2.6 mol% h-l), and the YP/s remained at maximum [26]. These results show that a useful range of copolymers can readily be formed by strain UWD growing in BM medium in the fermenter.…”
Section: Formation Of P(hb-co-hv) Copolymers In Beet Molasses Mediummentioning
confidence: 61%
See 2 more Smart Citations
“…1 g 1-~ hthe rate of HV synthesis was constant (approx. 2.6 mol% h-l), and the YP/s remained at maximum [26]. These results show that a useful range of copolymers can readily be formed by strain UWD growing in BM medium in the fermenter.…”
Section: Formation Of P(hb-co-hv) Copolymers In Beet Molasses Mediummentioning
confidence: 61%
“…Thus the likely intermediate leading to HV synthesis is the /3-ketoacyl-CoA intermediate prior to thiolysis. This speculation is supported by a detailed study of copolymer synthesis in strain UWD [26], which showed HV synthesis from 2-pentenoate, an intermediate in the/3-oxidation of valerate, and greatly increased HV formation from valerate in the presence of 4-pentenoate, a powerful inhibitor of/3-ketothiolase activity [27].…”
Section: Formation Of P(hb-co-hv) Copolymers In Beet Molasses Mediummentioning
confidence: 91%
See 1 more Smart Citation
“…P(3HB-co-3HV) has been produced in the cultivations of Ralstonia eutropha (R. eutropha) (5,(9)(10)(11), recombinant Escherichia coli (E. coli) (12,13), Paracoccus denitrificans and Methylobacterium extorquens (14), Azotobater vinelandii (A. vinelandii) UWD (15), A. latus (16), and Alcaligenes Sp. SH-69 (17) with several different carbon sources such as glucose and propionate, glucose and valerate, methanol and n-amyl alcohol, sucrose and valerate, butyrate and valerate, or only glucose, propanol, and valerate, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In PHA production by fermentation, the substrate and recovery costs are high, making their use unattractive. Page and his coworkers, using Azotobacter vinelandii UWD, have shown a substantial reduction in raw material cost using beet molasses (Page 1992 ;Page et al 1992).…”
Section: Introductionmentioning
confidence: 99%